Sequential administration of sclerostin antibody and parathyroid hormone differentially modulates fracture healing in a murine tibial osteotomy model - Atsushi Mihara; Kiminori Yukata; Norihiro Nishida; Tetsuya Seto; Ryuta Iwanaga; Kenzo Fujii; Kazuya Uehara; Yuji Saeki; Junji Ohgi; Shunya Tsuji; Masataka Asagiri; Takashi Sakai (PLoS ONE, 2026)
Anabolic agents such as parathyroid hormone (PTH) analogs and sclerostin antibody (Scl-Ab) enhance fracture healing through distinct mechanisms, but whether the order of administration affects healing remains unclear. In a murine tibial osteotomy model, we compared PTH monotherapy (40 μg/kg), Scl-Ab monotherapy (25 mg/kg), and two sequential regimens with matched treatment duration and cumulative exposure between sequential groups: PTH followed by Scl-Ab (PTH → Scl-Ab) and Scl-Ab followed by PTH (Scl-Ab → PTH). Treatment was started on postoperative day 1, and the sequential groups changed agents after 1 week. PTH monotherapy significantly increased mineralized callus volume, whereas Scl-Ab monotherapy produced higher callus volumetric bone mineral density (vBMD) and greater mechanical strength. Among the sequential regimens, Scl-Ab → PTH resulted in significantly higher callus vBMD and ultimate load to failure than PTH → Scl-Ab, despite comparable callus volumes. Histological analysis showed a higher proportion of cartilaginous tissue in the PTH monotherapy and PTH → Scl-Ab groups, suggesting persistence of an earlier phase of endochondral ossification. These findings indicate that early Scl-Ab administration followed by PTH promotes earlier callus mineralization and mechanical recovery than the reverse sequence in this murine model. Although the study was limited primarily to early healing time points, the results suggest that the temporal sequence of anabolic signaling, rather than agent selection alone, can influence early fracture repair.